Structure-tailored Mn-V oxide composite photocatalysts enabling enhanced photoelectrochemical oxygen evolution reaction - Radhalayam, D (ELSEVIER SCI LTD, 2026)
Photo-assisted electrocatalysis (PEC) is an innovative approach that enhances electrocatalytic efficiency by integrating light and electrical energy. The development of cost-effective, high-performance photocatalysts is essential to surmount the energy barriers in water splitting processes. In this work, Mn2V2O7/MnO2 composite nanostructures were prepared using a straightforward hydrothermal method with reaction durations of 6, 12, 18, and 24 h, labelled as Mn2V2O7/MnO2-6, Mn2V2O7/MnO2-12, Mn2V2O7/MnO2-18, and Mn2V2O7/MnO2-24, respectively. Among these, Mn2V2O7/MnO2-18 demonstrated superior photoelectrochemical performance, achieving a photocurrent density of 4.75 mA/cm2, which surpassed Mn2V2O7/MnO2-6, Mn2V2O7/MnO2-12, and Mn2V2O7/MnO2-24 by factors of 1.93, 1.53, and 1.12, respectively. The onset potentials for Mn2V2O7/MnO2-6, Mn2V2O7/MnO2-12, Mn2V2O7/MnO2-18, and Mn2V2O7/MnO2-24 were 0.467, 0.485, 0.445, and 0.456 V (vs. Ag/AgCl), with Mn2V2O7/MnO2-18 exhibiting the lowest onset potential. Transient photocurrent tests over 520 s under intermittent illumination confirmed excellent stability and reproducibility, with Mn2V2O7/MnO2-18 achieving the highest applied bias photon to current efficiency (ABPE). Additionally, Mn2V2O7/MnO2-18 displayed exceptional durability, sustaining performance for 7200 s under continuous illumination. These results highlight the significance of optimized hydrothermal synthesis in tailoring the structural and functional properties of Mn2V2O7/MnO2 composites, establishing Mn2V2O7/MnO2-18 as a robust and efficient photoelectrode for PEC water splitting.